Multimodality imaging with CT, MR and FDG-PET for radiotherapy target volume delineation in oropharyngeal squamous cell carcinoma. Issue 1 (December 2015) - Bird, David; Scarsbrook, Andrew; Sykes, Jonathan; Ramasamy, Satiavani; Subesinghe, Manil; Carey, Brendan; Wilson, Daniel; Roberts, Neil; McDermott, Gary; Karakaya, Ebru; Bayman, Evrim; Sen, Mehmet; et al.
Abstract Background This study aimed to quantify the variation in oropharyngeal squamous cell carcinoma gross tumour volume (GTV) delineation between CT, MR and FDG PET-CT imaging. Methods A prospective, single centre, pilot study was undertaken where 11 patients with locally advanced oropharyngeal cancers (2 tonsil, 9 base of tongue primaries) underwent pre-treatment, contrast enhanced, FDG PET-CT and MR imaging, all performed in a radiotherapy treatment mask. CT, MR and CT-MR GTVs were contoured by 5 clinicians (2 radiologists and 3 radiation oncologists). A semi-automated segmentation algorithm was used to contour PET GTVs. Volume and positional analyses were undertaken, accounting for inter-observer variation, using linear mixed effects models and contour comparison metrics respectively. Results Significant differences in mean GTV volume were found between CT (11.9 cm3 ) and CT-MR (14.1 cm3 ), p  < 0.006, CT-MR and PET (9.5 cm3 ), p  < 0.0009, and MR (12.7 cm3 ) and PET, p  < 0.016. Substantial differences in GTV position were found between all modalities with the exception of CT-MR and MR GTVs. A mean of 64 %, 74 % and 77 % of the PET GTVs were included within the CT, MR and CT-MR GTVs respectively. A mean of 57 % of the MR GTVs were included within the CT GTV; conversely a mean of 63 % of the CT GTVs were included within the MR GTV. CT inter-observer variability was found to be significantly higher in terms of position and/or volume than both MR and CT-MR (p  < 0.05). Significant differences in GTV volume were found between GTV volumes delineated by radiologists (9.7 cm3 ) and oncologists (14.6 cm3 ) for all modalities (p  = 0.001). Conclusions The use of different imaging modalities produced significantly different GTVs, with no single imaging technique encompassing all potential GTV regions. The use of MR reduced inter-observer variability. These data suggest delineation based on multimodality imaging has the potential to improve accuracy of GTV definition. Trial registration ISRCTN Registry:ISRCTN34165059 . Registered 2nd February 2015.